2016
DOI: 10.2169/internalmedicine.55.4957
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Diabetes Mellitus in Patients with Autoimmune Hepatitis

Abstract: Objective The administration of corticosteroids is a standard treatment for autoimmune hepatitis (AIH), but it can occasionally induce various adverse effects. Diabetes mellitus (DM) is a major complication of chronic liver diseases. We investigated the prevalence and risk factors of DM in patients with AIH. Methods We retrospectively analyzed 118 Japanese patients diagnosed with AIH from 1990 to 2014 at our institution. The prognosis of patients with and without DM was also compared. Results Twenty-nine (24.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Other complications of diabetes include liver diseases that are mainly caused by insulin resistance and oxidative stress (Bouderba et al ., ). Two hepatic complications are largely present in patients with diabetes: (i) concomitant autoimmune hepatitis (Matsumoto et al ., ) and (ii) NAFLD (Forlani et al ., ). A study of 118 diabetic patients found a prevalence of 24.5% of concomitant autoimmune hepatitis in diabetic patients (Matsumoto et al ., ).…”
Section: Hepatopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Other complications of diabetes include liver diseases that are mainly caused by insulin resistance and oxidative stress (Bouderba et al ., ). Two hepatic complications are largely present in patients with diabetes: (i) concomitant autoimmune hepatitis (Matsumoto et al ., ) and (ii) NAFLD (Forlani et al ., ). A study of 118 diabetic patients found a prevalence of 24.5% of concomitant autoimmune hepatitis in diabetic patients (Matsumoto et al ., ).…”
Section: Hepatopathymentioning
confidence: 99%
“…Two hepatic complications are largely present in patients with diabetes: (i) concomitant autoimmune hepatitis (Matsumoto et al ., ) and (ii) NAFLD (Forlani et al ., ). A study of 118 diabetic patients found a prevalence of 24.5% of concomitant autoimmune hepatitis in diabetic patients (Matsumoto et al ., ). NAFLD is a public health concern, the major treatment for which remains lifestyle changes, including weight reduction, the prevention of weight gain, a healthy diet, and physical activity (Zelber‐Sagi et al ., ).…”
Section: Hepatopathymentioning
confidence: 99%
“…The prev-▶table 3 Demographical, clinical, and metabolic comparison of patients with T1DM with or without AIH. alence of T3DM in patients with AIH being treated with corticosteroids is unknown [41]. In our analysis of 139 patients with AIH and diabetes, we found 7 patients with T3DM as a consequence of steroid treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Matsumoto et al analyzed 118 adult patients with AIH and found diabetes in 29 (24.5 %) patients, one of these having T1DM. Twenty-one (72.4 %) of the patients with diabetes received corticosteroids [41]. Otherwise, data on the occurrence of diabetes in patients with AIH undergoing treatment with corticosteroids are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…An association between T2D and AIH may therefore be anticipated. Yoneyama et al [32] found a prevalence of diabetes (type unspecified) of 37·9% in 29 AIH patients receiving corticosteroids, and Matsumoto et al [33] found a prevalence of diabetes (primarily T2D) of 24·5% in 118 AIH patients, 72·4% of whom receiving corticosteroids. Corticosteroids and a lower platelet count were associated with the new onset of diabetes, and patients with AIH and diabetes were significantly older, had a higher proportion of male sex, were less likely to have other autoimmune diseases, had lower platelet count, and had higher IgG levels than did patients with AIH without diabetes.…”
Section: Diabetes In Patients With Autoimmune Hepatitismentioning
confidence: 99%